Interpreting the Content of Processes for Supporting Investment - Vitiuk Anna V. (Problemi Ekonomiki, 2018)
The theoretical and applied bases of the formation and development of processes for supporting investment of enterprises are studied. In particular, a terminological analysis of interpreting the categories of “supporting processes” and “processes for supporting investment” is carried out, and conceptual differences in the interpretation of these categories are determined in accordance with the theories of various economic schools and the domestic regulatory framework. The paper stresses the need to develop processes for supporting investment as a way to provide the basis for economic activity and accelerate high rates of public production. It is proved that the supporting processes include various aspects of implementation of investments. The necessity of breaking down the processes for supporting investment into basic and auxiliary ones is substantiated. It is established that the basic processes for supporting investment should include the processes of institutional, organizational, and financial security. The auxiliary process for supporting investment are proposed to be subdivided into the processes of staffing, infrastructural, informational, marketing, technical and technological, and resource support. It is proved that the implementation of investments should be based on compliance with the requirements of normative legal acts (regulatory support) of a particular region where the investment is realized. State measures in the field of investment should unite the social and economic, and regulatory environment of enterprises and be characterized by consistency and logical completeness (institutional support). It is established that in accordance with the following requirements, there should be formed an organizational structure, which will be entrusted the responsibilities of the real implementation of investments (organizational support) that should be properly financed (financial support). The carrying out of such activities implies a certain mechanism utilized through the auxiliary processes for supporting investment.